Limitations of Big Data Partitions Technology - Trang, Nguyen Huyen (Bright Publisher, 2020)
Big data is defined as the amount of data that is needed by new technology and architecture so that it is possible to extract the large amount of data provided by the analysis process. Due to its enormous size it is increasingly difficult for perfect analysis using existing traditional techniques. This technology is a solution for several problems that require a distributed system for storage needs because a problem cannot be solved in one machine. Since Big Data has become the latest technology in a market that brings tremendous profits to business organizations, it becomes possible when there are specific challenges and problems and it will continue to expand. This article introduces big data technology, and explains its partition limitations.